2017
DOI: 10.5296/jas.v5i3.11881
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Fertilization Of Corn (Zea mays L.) Cultivated on Ferrous Soil in Southern Benin

Abstract: The attainment of the millennium for development objectives require to improve the productivity of major cultures like maize (Zea mays L.). The present study aimed to assess the potential of Glomus cubens, Rhizophagus intraradices and Funneliformis mosseae to improve the productivity of corn cultivated on reddish ferrous soil in Southern Benin. A block of nine treatments with four repetition completely randomized was installed. Plant height and diameter and leaf area are growth parameters measured. Grain yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
2
5
0
1
Order By: Relevance
“…Fertilization with 30 kg P2O5 ha -1 seemed to be sufficient to improve the nutritional status of the Ferralsol used as substrate for this experiment, compared to the dose of 60 kg P2O5 ha -1 which is low cost effectiveness. These results are nearing those found by Aguegue et al (2017) in Ferralsol in southern Benin, indicating that Glomus cubens species combined to a half dose of chemical fertilizers of NPK (7.5 P2O5 kg ha -1 ) allow to get an equivalent production of maize to that obtained using the recommended dose of NPK (15 P2O5 kg ha -1 ) alone. The AMF inoculum alone given cobs well filled with grains, thus much better than plants of the control (without phosphorus neither AMF inoculum) given cobs without grains.…”
Section: Yield Parameters and Grains Phosphorus Contentsupporting
confidence: 61%
See 1 more Smart Citation
“…Fertilization with 30 kg P2O5 ha -1 seemed to be sufficient to improve the nutritional status of the Ferralsol used as substrate for this experiment, compared to the dose of 60 kg P2O5 ha -1 which is low cost effectiveness. These results are nearing those found by Aguegue et al (2017) in Ferralsol in southern Benin, indicating that Glomus cubens species combined to a half dose of chemical fertilizers of NPK (7.5 P2O5 kg ha -1 ) allow to get an equivalent production of maize to that obtained using the recommended dose of NPK (15 P2O5 kg ha -1 ) alone. The AMF inoculum alone given cobs well filled with grains, thus much better than plants of the control (without phosphorus neither AMF inoculum) given cobs without grains.…”
Section: Yield Parameters and Grains Phosphorus Contentsupporting
confidence: 61%
“…The same average was obtained for plant height, leaves number and chlorophyll rate in leaves especially on treatments inoculated and fertilized with 30 or 60 kg P2O5 ha -1 . This joins the allegations of Davies and Linderman (1990) and Aguegue et al (2017) showing that the only micro-doses of chemical fertilizers (half of the crop demand) are sufficient to promote plant growth when AMF have been applied. Munir et al (2003) also showed that the addition of phosphorus decreases the mycorrhizal symbiosis because the plant's growth depends on the chemical fertilizer.…”
Section: Discussionmentioning
confidence: 62%
“…These results agree with those observed by Bulakali et al (2000), who showed in their study that mycorrhizal fungi had a beneficial effect on the growth in diameter at the collar of corn plants. The same observations were made by Aguegue et al (2017), who showed that the inoculation of corn seeds by mycorhizal fungi had a beneficial effect on the diameter at the collar of the treated plants compared to the control. Previous studies have shown that the presence of mycorrhizal fungi stimulate the growth of the leaf surface of corn plants (Kothari et al, 1990).…”
Section: Discussionsupporting
confidence: 76%
“…The genus Glomus is the most represented in all sites with 15 morphotypes (65%). Such a result has been noted in different natural and agro-ecological environments in West Africa as well as in Ivory Coast (Anguiby et al, 2019), in Togo (Gnamkoulamba et al, 2018), in Benin (Aguegue et al, 2017), in Senegal (Diop et al, 2015), and in India (Ajaz et al, 2017). Indeed, it has been reported that the genus Glomus predominates in terms of presence in ecosystems due to its adaptability and stability in tropical environments and various conditions (Lenoir et al, 2016b;Bencherif et al, 2015).…”
Section: Discussionmentioning
confidence: 66%